Analysis of the Construction Form of an Electrical Car Chassis Prototype Type Hollow Alumunium 6061 Pipe Profile Using Inventor Software 2019 - Aep Surahto; Riyan Ariyansah; Fathoni; Qommaruddin; Agus Fikri; Mohammad Mujirudin; Arry Avorizano; Goodman Octavianus (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
The chassis is a critical structural component in vehicle design, especially in electric vehicle (EV) development aimed at reducing environmental impact. This study analyzes the structural performance of a prototype electric vehicle chassis made from 6061 hollow aluminum using Autodesk Inventor 2019. Three chassis models were designed and tested under a static load of 900 N to compare stress distribution, displacement, and safety factors. All chassis designs had dimensions of 2160 mm × 750 mm × 500 mm with a wall thickness of 2 mm. Simulation results showed that the H-type chassis model performed best, with a von Mises stress of 36.03 MPa, displacement of 4.28 mm, and a safety factor of 7.63. These results indicate that the H-type chassis is structurally safe and suitable for prototype application.